Wireless Electroencephalography Based Blood Pressure Monitoring - A. Jafri, R.; Shahid, N.; F. Shamim, M.; A. Alam, M.; W. Munir, M.; Z. Ul Haque, M. (International Journal of Engineering and Technology, 2018)
The number of cardiac patients and aged individuals are at a rise all around the world. Taking care of such individuals is a major challenge these days. In many cases, these patients require special care and regular monitoring of vital signs like blood pressure (BP). Focusing a prevalent idea of wireless brain-computer interface (WBCI), an innovative research work is considered to meet essential routine monitoring of BP for cardiac patients and aged people without any reliance. The research framework involves the use of wireless electroencephalogram (EEG) headset to control wrist BP and arm BP monitors to determine accurate BP readings in the proposed system. An Android application "Smart Home Monitor" is developed that screens the information from the headset. The research framework is tested on ten individuals to examine the precision in BP readings from two different BP monitors. Results specify that both upper arm blood pressure readings i.e. Systolic BP readings (SBP = 119.6 Â±5.1 mmHg) and Diastolic BP (DBP = 79.5 Â±7.4 mmHg) were found to be better than the wrist BP readings (SBP = 128.2 Â±11.7 mmHg and DBP = 83.6 Â±10.3 mmHg). This examination assessed that the designed system empowers the framework to be reliable, remote and compact.Â Â